Local Labor Market Conditions and the Jobless Poor: How Much Does Local Job Growth Help in Rural Areas? - Elizabeth E. Davis; Laura S. Connolly; Bruce A. Weber (Journal of Agricultural and Resource Economics, 2003)
The employment outcomes of a group of jobless poor Oregonians are tracked in order to analyze the relative importance of local labor market conditions on their employment outcomes. Local job growth increases the probability that a jobless poor adult will get a job and shortens the length of time until she finds a job. After accounting for both the effects of personal demographic characteristics and local job growth, there is little evidence that the probability of employment or the duration of joblessness differs in rural compared with urban areas.